The structure, stratigraphy and hydrocarbon potential of the onshore early Cretaceous Basin, West-Gippsland, Victoria, Australia - Aghaei, Hamed (Monash University. Faculty of Science. School of Earth, Atmosphere and Environment, 2015)
The Gippsland Basin, one of the largest Australian oil and gas basins, is located in southeast Australia where it lies across the Palaeozoic Tasman Fold Belt. It developed during Early and Late Cretaceous, north-south lithospheric extension between Australia and Antarctica, and the Late Cretaceous separation of Australia from the Lord Howe Rise/Campbell Plateau. The Strzelecki Group, the oldest unit in the Gippsland Basin, was deposited between ~150 Ma (Tithonian) and ~100 Ma (Albian), as a result of Early Cretaceous extension associated with the development of the rift basin bounded by the Foster and Lake Wellington faults. It mainly consists of interbedded mudstones, sandstones and coal beds. This group plays the role of basement in eastern part of the basin, however, it experienced uplift to the west that provides spectacular outcrops especially along the coastal area between San Remo and Inverloch. There are still questions regarding structure, stratigraphy and hydrocarbon potential of this group in the Gippsland region. The present day thickness of this group in the west Gippsland area and the amount of erosion during Late Cretaceous uplift is still controversial, the structural framework is not well known and the hydrocarbon potential was not well evaluated in the past. The present study mainly focused on unique coastal outcrops of Strzelecki Group in the Wonthaggi area of west Gippsland to interpret their structure, stratigraphy and hydrocarbon source potential via extensive field work including mapping, logging, sampling, and also interpreting the results of optical and instrumental analyses on thermal maturity, spore-pollen zone and source potential. It has been revealed that the outcrops are non-marine, interbedded mudstone and fine-medium grained sandstone with numerous coal beds. Three generations of faults have been mapped, which, in chronological order from oldest to youngest, have dominant trends of E-W, NW-SE and NE-SW. The section is intruded by a number of dominantly NW trending dykes which vary in thickness from less than 0.5 m to more than 2 m. Vitrinite reflectance measurements of fifty-five samples reveal that the outcrops vary in VR from 0.42% to 0.76% in unaffected areas. Palynology reveals the oldest part of section is located NW of Harmers Haven and east of the Oaks within the spore-pollen zone of P.notensis and F.wonthaggiensis. A stratigraphic thickness of at least 1.4 km has been recorded along about 20 km of coastline from northwest of Harmers Haven to west of Inverloch; and then a stratigraphic column of this highly faulted area was reconstructed based on palynology, vitrinite reflectance data and a palaeo-geothermal gradient of 50 oC/km. Although no sediment section greater than 200 m thick is exposed in any one fault block, a total thickness of 1000 m is inferred to be exposed between Harmers Haven and Inverloch. However, because of the amount of faulting and probable repeated sections, the true thickness of upper Strzelecki Group exposed in the coastal outcrops is only about 300 m. This compares closely with the maximum thickness of about 400 m encountered in eight drill holes that penetrated to Palaeozoic basement in the eastern Wonthaggi coalfield. Based on palynology results, the reconstructed Strzelecki Group stratigraphic column has been classified into three distinct “bio-blocks”, with a range of eroded section from 1.5 km (0.3-2.6 km at ±95% confidence limits) to 2.7 km (2.2-3.1 km at ±95% confidence limits) modified from extrapolation of estimated palaeogeothermal gradient into an assumed palaeosurface temperature of 15 oC. Rock-Eval analysis was carried out in order to estimate the source potential of those units with a significant organic content. In addition, data from a number of petroleum bores were interpreted in order to get better regional understanding of Strzelecki Group hydrocarbon potential. Total organic content (TOC) of fifty-two outcrop samples ranges between 0.2%-73.4%, with coal units having much higher values compared to the mudstones. Rock-Eval analysis on 19 samples with significant TOC suggests Type II/III are the dominant kerogens, with maturity ranges between immature to early-mature. Organic petrography reveals Type III as the dominant kerogen, with local traces of kerogen Type I. Well data from Megascolides-2, about 50 km north of Wonthaggi township, indicates Type III kerogen is dominant and places the intersected Strzelecki Group in the early to late mature zone, while data from Loy Yang-1A, about 95 km east of Wonthaggi, suggest dominant Type II/III of kerogen for the intersected Strzelecki Group and places it into the early-peak to late maturity zone. To evaluate the impact of the igneous intrusions on the adjacent sediments, a detailed study of the contact metamorphism has been undertaken using the vitrinite reflectance measurements. Twenty two representative organic-rich mudstone samples have been collected on both sides of one of the intrusions in southeast of the Harmers Haven area. The dykes vary in thickness between 0.67-1.4 m, however, at the point of sampling the thickness was about 1 m. The samples were collected at the distance of up to 25 m East and West from the dyke margins. In addition, type of intrusion was modified from conventional thin section petrography, and major and trace elements. Optical analysis reveals that these medium grained porphyritic rock samples are dominated by phenocrysts of augite and olivine, in a groundmass of plagioclase, augite and olivine. Phenocrysts comprises up to ≈ 10% by volume of the rock, although abundances are variable from sample to sample. Olivine phenocrysts are subhedral to euhedral. In some of the samples olivine is partially to completely altered to serpentine. Augite phenocrysts are also subhedral to euhedral. The groundmass of the rock consists of plagioclase laths, commonly elongate and with a poorly developed variolitic texture. In addition, based on the results of major and trace element analysis the intrusion was classified as an alkali basalt. The vitrinite reflectance of up to 6.67% [Rmax] was recorded at the dyke contacts and decreased to the background level of around 0.75% - 0.80% [Rmax] within a distance of 5 m from the dyke margins. These observations suggest that the thermal maturity of the sediments in the Harmers Haven area was elevated by the heating due to the emplacement of the intrusive. The results of the present study indicate that the extent of the thermal aureoles as indicated by vitrinite reflectance measured on samples collected west from the intrusion margin is at least twice the thickness of the dyke, while a slightly different pattern is observed on the eastern site.